2018
DOI: 10.1007/s10072-018-3307-4
|View full text |Cite
|
Sign up to set email alerts
|

Lower uric acid is associated with poor short-term outcome and a higher frequency of posterior arterial involvement in ischemic stroke

Abstract: Uric acid has neuroprotective properties in experimental and clinical studies of neurodegenerative disease. It is, however, associated with increased risk of stroke, yet, despite some inconsistent findings, increasing evidence suggests it may also be related to improved stroke outcomes. We have determined whether there is an effect of plasma uric acid on the short-term outcome of stroke patients in a general hospital setting using the modified Rankin Scale (mRS). We also investigated the relationship of uric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The major circulating antioxidant in the human body is uric acid (UA) (Bowman et al 2010). Although elevated UA increases the risk of cardiovascular disease and stroke, it appears to have neuroprotective properties as it is found to be reduced in patients with several neurodegenerative disorders, including Alzheimer's (Khan et al 2016;Mullan et al 2018) and Parkinson's diseases (Shen et al 2013), as well as being associated with outcome of ischaemic stroke (Liu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The major circulating antioxidant in the human body is uric acid (UA) (Bowman et al 2010). Although elevated UA increases the risk of cardiovascular disease and stroke, it appears to have neuroprotective properties as it is found to be reduced in patients with several neurodegenerative disorders, including Alzheimer's (Khan et al 2016;Mullan et al 2018) and Parkinson's diseases (Shen et al 2013), as well as being associated with outcome of ischaemic stroke (Liu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of cognitive function after AIS was performed during the hospitalization in six studies 20 22 24 25 26 27 , and during follow-up after discharge in the other five studies 21 23 28 29 30 . Diagnosis of PSCI was based on the Mini-mental State Examination (MMSE) in two studies 20 28 , the Montreal Cognitive Assessment (MoCA) in seven studies 21 22 24 25 26 29 30 , and MMSE or MoCA in one study 27 . The other study reported two datasets of serum UA values for PSCI diagnosed with MMSE and MoCA, separately 23 .…”
Section: Resultsmentioning
confidence: 99%
“…UA after AIS may be associated with PSCI [19]. However, results of previous studies comparing the serum level of US between patients with and without PSCI showed inconsistent results [20][21][22][23][24][25][26][27][28][29][30], and the association between serum UA and PSCI in patients with AIS remains to be determined. Therefore, in this study, we performed a meta-analysis to systematically evaluate the association between serum UA and PSCI in patients with AIS.…”
Section: Uric Acid and Cognitive Impairment In Patients With Acute Is...mentioning
confidence: 99%
“…The neuroprotective effects of UA can be explained in the following ways: (1) UA has an antioxidative effect, preventing the cerebrovascular system from being damaged by oxidative stress [ 21 , 22 ]. (2) UA can remove oxidative free radicals caused by chelation of metal ions and increase the metabolism of purine in the brain [ 23 ]. (3) UA protects local cerebral blood supply by activating the expression of neurotrophic factors and reduces brain damage caused by reperfusion [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%